Problems and Methods of Control in Transportation Systems - Cenek, Petr (Communications - Scientific letters of the University of Zilina, 2000)
The basic idea of the article is to show various problems of control and management in transportation systems and the necessity of an available information support. The importance of transportation and some ideas on its significance for a modern society is reflected in the paper. The model of a transportation system is further described together with some optimisation problems and methods how to solve them. The necessity of a generalisation of a data model and standardisation of data on the transportation infrastructure as well as statistical data on transportation flows is stressed as abasic need for any exact method of control in transportation systems.